Verrucous venous malformation (formerly verrucous hemangioma): a difficult to classify vascular lesion. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2022)
errucous venous malformation (VVM) is a rare, early onset, segmental, often localized to one leg disease, characterized by lesions apparently similar to port-wine stain, which over time become hyperkeratotic and do not regress, may ulcerate or undergo localized intravascular coagulation (5). As evidenced by its history and its previous denomination of verrucous hemangioma (VH), in the recent past VVM presented difficulties in its nosological classification. The latter were partly linked to the clear distinction between hemangiomas and vascular malformations […].